Acid-resistant atomic-scale dispersed cobalt carbon nitrogen catalyst as well as preparation method and application thereof

By preparing an acid-resistant atomic-grade dispersed cobalt carbon-nitrogen catalyst, the problem of Rainey nickel catalyst in the prior art is solved, high activity and stability under acidic conditions are achieved, acidic wastewater and metal residues are reduced, and the residues of acidic wastewater and metals are improved. Drug yield, suitable for green drug production.

CN119425755APending Publication Date: 2025-02-14HEBEI UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411567050.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The Rainey nickel catalyst used in the production of xanthine drugs in the prior art is not acid resistant, resulting in a decrease in catalytic activity, an increase in metal residues and excessive discharge of acidic wastewater. The cost of precious metal catalysts is high, and there are safety risks.

Method used

Acid-resistant atomic dispersed cobalt carbon-nitrogen catalyst (CoSA/CN) was prepared by mixing-drying-baking technology. The reaction of a mixed solution of cobalt nitrate hexahydrate and zinc nitrate hexahydrate and 2-methylimidazole to form a purple precipitate. , after high-temperature calcination and acid etching treatment, a stable atomic-scale dispersed cobalt carbon-nitrogen catalyst was obtained.

Benefits of technology

The catalyst has high activity, stability and multiple recycling capabilities under acidic conditions, reducing acidic wastewater discharge and metal residues, improving the yield of dimethyl-DAU, and is suitable for the green production of xanthine drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005119518640000011
    Figure HDA0005119518640000011
  • Figure HDA0005119518640000012
    Figure HDA0005119518640000012
  • Figure HDA0005119518640000021
    Figure HDA0005119518640000021
Patent Text Reader

Abstract

The invention provides an acid-resistant atomic-scale dispersed cobalt carbon nitrogen catalyst as well as a preparation method and application thereof. The invention discloses a preparation method of a catalyst for catalytic hydrogenation of N, N-1, 3-dimethyl-4, 5-diamino urea azine (dimethyl-NAU) under an acidic condition. The scheme belongs to the technical field of green chemistry and chemical engineering. According to the technical scheme, the preparation method is characterized in that a cobalt and zinc bimetal organic framework material is used as a precursor, and the atomic-scale dispersed cobalt-carbon-nitrogen (CoSA / CN) catalyst is prepared through roasting in an inert gas atmosphere. The catalyst is simple in preparation process, high in acid resistance and long in service life. Under the acidic condition, the catalyst has good dispersity in the dimethyl-NAU hydrogenation reaction, and has the characteristics of high activity, good selectivity, high stability, easiness in separation and recycling, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of green chemistry and chemical engineering, and in particular to an acid-resistant atomic-level dispersed cobalt carbon-nitrogen catalyst and a preparation method and application thereof. Background Art

[0002] 1,3-Dimethyl-4,5-diaminourea zine (dimethyl-DAU) is an important intermediate in the production of xanthine drugs. Xanthine drugs include caffeine, theophylline, aminophylline, doxofylline, theobromine, pentoxifylline, 2-hydroxypropylphylline, etc. They are commonly used drugs for the treatment of central nervous system, cardiovascular system and bronchial system diseases. Caffeine is also used as an additive in functional beverages.

[0003] At present, the Raney nickel catalytic hydrogenation method is often used in industry to reduce 1,3-dimethyl-4-imino-5-isonitrosourea zine (dimethyl-NAU) to dimethyl-DAU. However, dimethyl-NAU is generally prepared by nitrosation of 1,3-dimethyl-4-iminouracil in a strongly acidic environment, and the resulting dimethyl-NAU needs to be washed with water to remove residual sulfuric acid and sodium nitrite. If a large amount of water is used to wash the crude product to neutrality, a large amount of product will be lost with the water, and a large amount of acidic wastewater will be generated; if a small amount of water is used to wash the crude product, the acidic substance will enter the next step of dimethyl-DAU hydrogenation reaction. This part of the acidic substance not only etches the Raney nickel catalyst to greatly reduce the catalytic activity, but also leaves a large amount of nickel metal residue in the product. In addition, the Raney nickel catalyst has poor dispersibility in the autoclave reactor and often aggregates into blocks, which greatly reduces the catalytic activity.

[0004] In the patent application document (CN 113058590 A), in the preparation of dimethyl-DAU using a wet-based carbon-supported nano-precious metal catalyst, the catalyst preparation method is: using acid-pretreated activated carbon as a carrier, using an impregnation method to prepare a Pd-supported activated carbon catalyst, then adding an activity regulator for aging treatment, and finally filtering water for rinsing to obtain a wet-based carbon-supported palladium catalyst. Under the action of this catalyst, the yield of dimethyl-NAU hydrogenation to dimethyl-DAU is greater than 96%, but the catalyst is a precious metal catalyst, which is costly and not conducive to industrial production.

[0005] In the patent application document (patent CN 104003941 A), an aqueous solution containing metal halides and alkaline substances is used as the reaction medium, and the yield of dimethyl-NAU hydrogenation reaction can reach 94.5%. However, it uses Raney nickel as a catalyst, which is easy to spontaneously combust in the air, and there are great safety risks in the production and use process. In addition, the Raney nickel catalyst is not acid-resistant and quickly deactivates under acidic conditions.

[0006] Therefore, in the production process of dimethyl-DAU, the development and use of acid-resistant catalysts with high activity, high safety and good stability can effectively reduce the discharge of acidic wastewater, reduce metal residues in the product and increase product yield, which is of great significance to the green production of xanthine compounds and the improvement of production efficiency. Summary of the invention

[0007] The purpose of the present invention is to provide an acid-resistant atomic-level dispersed cobalt carbon nitrogen catalyst and a preparation method and application thereof. The catalyst has good dispersibility, high activity and good stability in the dimethyl-NAU hydrogenation reaction, can be recycled for multiple times under acidic conditions, can effectively reduce the discharge of acidic wastewater, reduce metal residues in products and improve product yield.

[0008] The present invention is achieved in that:

[0009] An acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst (Co SA / CN) preparation method, comprising the following steps:

[0010] (1) Dissolving cobalt nitrate hexahydrate and zinc nitrate hexahydrate in a solvent to obtain a mixed metal salt solution; dissolving 2-methylimidazole in a solvent to obtain a 2-methylimidazole solution; adding the mixed metal salt solution dropwise to the 2-methylimidazole solution, and stirring at room temperature for 30 minutes; collecting the obtained purple precipitate, centrifuging it, washing it twice with ethanol, and vacuum drying it to obtain a purple powder.

[0011] (2) The purple powder obtained in step (1) is placed in a tube furnace, heated at a high temperature of 5°C / min in flowing nitrogen, kept at a constant temperature, and then naturally cooled to room temperature to obtain a black solid powder.

[0012] (3) The black powder obtained in step (2) is etched in an acidic solution to obtain an atomically dispersed cobalt carbon nitrogen catalyst.

[0013] In step (1), the molar ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is 1:1 to 1:15, preferably 1:10.

[0014] In step (1), the solvent selected is methanol.

[0015] In step (1), the molar ratio of the mixed metal salt to 2-methylimidazole is 1:2 to 1:5, preferably 1:4.

[0016] In step (2), the calcination temperature in nitrogen is 700-1100° C., preferably 800° C.; the constant temperature holding time is 1-4 hours, preferably 3 hours.

[0017] In step (3), the acidic solution is hydrochloric acid or sulfuric acid, preferably sulfuric acid; the acidic condition is pH = 1 to 2, preferably pH = 1; the volume ratio of the mass of the black solid powder to the acidic solution is 1 to 5:1 mg / mL, preferably 3:1 mg / mL; the etching time is 12 to 48 hours, preferably 24 hours.

[0018] The catalyst prepared by the method of the present invention is applied to the hydrogenation reaction of dimethyl-NAU under acidic conditions, and the experimental conditions are as follows:

[0019] Dimethyl-NAU, catalyst, and sulfuric acid solution (20 mL) with pH = 1 to 4 were added to a polytetrafluoroethylene autoclave in sequence, sealed, and the air was replaced with H2 for 3 to 6 times, and then H2 was introduced to 1.0 MPa. The reaction system was maintained at 20 to 80°C for 2 hours with a stirring speed of 400 rpm. After the reaction was completed, the obtained reaction solution was analyzed by liquid chromatography. The catalyst was recovered by centrifugation and the next recycling experiment was carried out.

[0020] Compared with the prior art, the technical effects achieved by the present invention are as follows:

[0021] The acid-resistant atomic-level dispersed cobalt carbon-nitrogen catalyst provided by the present invention is prepared by a mixing-drying-calcining process, which is simple and safe to operate. Under acidic conditions, the catalyst has stable structure and properties, good dispersibility, high activity and good stability in aqueous phase reactions, and the catalytic performance remains stable after multiple cycles of use, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The catalyst Co in Example 1 of the present invention SA BET spectrum of / CN.

[0023] Figure 2 The catalyst Co in Example 1 of the present invention SA / CN X-ray powder diffraction (XRD) spectrum.

[0024] Figure 3 In the embodiment 1, (a) is the catalyst Co SA / CN at 50nm size transmission electron microscope (TEM); (b) is the catalyst Co in Example 1 SA / CN at 20nm size; (c) is the TEM image of catalyst Co in Example 1 SA Spherical aberration corrected high-resolution transmission electron microscopy (AC-HAADF-STEM) image of / CN.

[0025] Figure 4 The catalyst Co in Example 1 of the present invention SA / CN recycling effect diagram under pH=3.05 conditions.

[0026] Figure 5 The catalyst Co in Comparative Example 1 of the present invention NP / CN-1 recycling effect diagram under pH=3.05 conditions.

[0027] Figure 6 The catalyst Co in Comparative Example 2 of the present invention NP / CN-2 recycling effect diagram under pH=3.05 conditions.

[0028] Figure 7 This is a diagram showing the recycling effect of commercially available Raney nickel under the condition of pH=3.05 in Comparative Example 3 of the present invention.

[0029] Figure 8 The catalyst Co in Example 1 of the present invention SA Comparison of the recycling effects of CN and commercially available Raney nickel under pH = 1.95. DETAILED DESCRIPTION

[0030] Example 1

[0031] Co SA Preparation of / CN catalyst: 0.32g Co(NO3)2·6H2O and 3.24g Zn(NO3)2·6H2O (Co:Zn=1:10) were mixed and dissolved in 120mL methanol as solution 1. Then, 4.02g 2-methylimidazole was dissolved in 40mL methanol as solution 2. Solution 1 was dropped into solution 2 and stirred at room temperature for 30min. The obtained precipitate was collected by centrifugation at 8000rpm for 5min, washed twice with ethanol, and dried in vacuum at 60℃ overnight. The powder prepared above was placed in a tubular furnace, heated to 800℃ at a rate of 5℃ / min in flowing nitrogen, and kept warm for 3h, and then cooled naturally to room temperature. 60mg of the obtained catalyst was placed in 20mL sulfuric acid solution (pH=1) and etched for 24h, and vacuum dried at 60℃ to obtain an acid-resistant atomic-level dispersed cobalt carbon nitrogen catalyst, recorded as Co SA / CN (subscript SA means single atom).

[0032] The catalyst Co obtained in this example SA / CN conducted nitrogen adsorption and desorption tests and pore size analysis. The results are as follows Figure 1 As shown, Co SA / CN catalyst has a higher specific surface area (859.7m 2 / g), and its isotherm belongs to the typical IV type isotherm. In the high pressure distribution range, there is an obvious H4 type hysteresis loop, which proves that in Co SA There are a large number of mesoporous structures in the / CN catalyst.

[0033] The catalyst Co obtained in this example SA / CN were analyzed by inductively coupled plasma emission spectroscopy. The results showed that Co SA The Co content in the / CN catalyst is 4.9wt%.

[0034] The catalyst Co obtained in this example SA / CN conducted XRD test, the results are as follows Figure 2 As shown. Figure 2 It can be seen that Co SA / CN catalyst did not show the characteristic diffraction peak of metallic cobalt, indicating that Co SA In / CN, metallic Co is highly dispersed on the carbon nitride support.

[0035] The catalyst Co obtained in this example SA / CN conducted transmission electron microscopy test, and the results were as follows Figure 3 shown. Figure 3 In the figure, (a) and (b) are Co SA Transmission electron microscopy (TEM) images of the / CN catalyst at different magnifications. No Co nanoparticles or nanoclusters were found in the TEM images, indicating that Co SA The cobalt atoms in the / CN catalyst are dispersed on the carbon nitride support at the atomic level. Figure 3 (c) Co SA The spherical aberration corrected high-resolution transmission electron microscopy (AC-HAADF-STEM) image of the / CN catalyst further confirmed that metallic cobalt existed in the form of single atoms.

[0036] The catalyst Co obtained in this example SA / CN acid resistance test: Under the condition of pH = 3.05, the catalyst Co prepared above was selected SA / CN was used to perform dimethyl-NAU hydrogenation experiments as follows:

[0037] Dimethyl-NAU (85 mg), Co SA / CN catalyst (40 mg) and sulfuric acid solution (20 mL) with pH = 3.05 were added to a 50 mL polytetrafluoroethylene autoclave in sequence, sealed, replaced with H2 for 3 to 6 times, and then H2 was introduced until the partial pressure reached 1.0 MPa. The reaction system was maintained at 40°C for 2 h with a stirring speed of 400 rpm. After the reaction was completed, the reaction solution was analyzed by liquid chromatography. The catalyst Co was recovered by centrifugation SA / CN, and then conduct the next cycle use experiment. And so on, after several cycles of use, the test results are as follows Figure 4 As shown. Figure 4 It can be seen that the Co obtained in this embodiment SAAfter the / CN catalyst was recycled for 10 times under the condition of pH=3.05, the conversion rate could be maintained at around 55% without obvious decline.

[0038] The catalyst Co obtained in this example SA / CN was subjected to dimethyl-NAU hydrogenation experiment at pH = 1.95. Specifically, dimethyl-NAU (85 mg), Co SA / CN catalyst (40 mg) and sulfuric acid solution (20 mL) with pH = 1.95 were added to a 50 mL polytetrafluoroethylene autoclave in sequence, sealed, replaced with H2 for 3 to 6 times, and then H2 was introduced until the partial pressure reached 1.0 MPa. The reaction system was maintained at 40°C for 2 h with a stirring speed of 400 rpm. After the reaction was completed, the reaction solution was analyzed by liquid chromatography. The catalyst Co was recovered by centrifugation SA / CN, and then conduct the next cycle use experiment. And so on, after several cycles of use, the test results are as follows Figure 8 As shown. Figure 8 It can be seen that the Co obtained in this embodiment SA After the / CN catalyst was recycled for 10 times under the condition of pH=1.95, the conversion rate decreased slightly, indicating that it has good stability.

[0039] Comparative Example 1

[0040] Co NP Preparation of / CN-1 catalyst: 1.78g Co(NO3)2·6H2O and 1.82g Zn(NO3)2·6H2O (Co:Zn=1:1) were mixed and dissolved in 120mL methanol as solution 1. Then, 4.02g 2-methylimidazole was dissolved in 40mL methanol as solution 2. Solution 1 was dropped into solution 2 and stirred at room temperature for 30min. The obtained precipitate was collected by centrifugation at 8000rpm for 5min, washed twice with ethanol, and dried in vacuum at 60℃ overnight. The powder prepared above was placed in a tubular furnace, heated to 800℃ at a rate of 5℃ / min in flowing nitrogen, and kept warm for 3h, and then cooled naturally to room temperature. 60mg of the obtained catalyst was placed in 20mL sulfuric acid solution (pH=1) and etched for 24h, and dried in vacuum at 60℃ to obtain a cobalt carbon nitrogen catalyst, recorded as Co NP / CN-1 (the subscript NP stands for nanoparticles).

[0041] The catalyst Co obtained in this comparative example NP / CN-1 was analyzed by inductively coupled plasma emission spectroscopy. The results showed that Co NP The Co content in the / CN-1 catalyst is 27.86wt%.

[0042] The catalyst Co obtained in this comparative example NP / CN-1 was tested for acid resistance: Under pH=3.05, the prepared catalyst Co NP / CN-1 was subjected to dimethyl-NAU hydrogenation experiment as follows:

[0043] Dimethyl-NAU (242 mg), Co NP / CN-1 catalyst (20 mg) and sulfuric acid solution (20 mL) with a pH of 3.05 were added to a 50 mL polytetrafluoroethylene autoclave in sequence, sealed, replaced with H2 for 3 to 6 times, and then H2 was introduced until the partial pressure reached 1.0 MPa. The reaction system was maintained at 40°C for 2 hours with a stirring speed of 400 rpm. After the reaction was completed, the reaction solution was analyzed by liquid chromatography. The catalyst was recovered by centrifugation and the next recycling experiment was carried out. Similarly, the test results after several cycles are shown in the figure below. Figure 5 As shown. Figure 5 It can be seen that the catalyst Co prepared in this comparative example NP The conversion rate of / CN-1 decreased by 33.8% after 8 cycles.

[0044] Comparative Example 2

[0045] Co NP Preparation of / CN-2 catalyst: 0.58g Co(NO3)2·6H2O and 3.03g Zn(NO3)2·6H2O (Co:Zn=1:5) were mixed and dissolved in 120mL methanol as solution 1. Then, 4.02g 2-methylimidazole was dissolved in 40mL methanol as solution 2. Solution 1 was dropped into solution 2 and stirred at room temperature for 30min. The obtained precipitate was collected by centrifugation at 8000rpm for 5min, washed twice with ethanol, and dried in vacuum at 60℃ overnight. The powder prepared above was placed in a tubular furnace, heated to 800℃ at a rate of 5℃ / min in flowing nitrogen, and kept warm for 3h, and then cooled naturally to room temperature. 60mg of the obtained catalyst was placed in 20mL sulfuric acid solution (pH=1) and etched for 24h, and dried in vacuum at 60℃ to obtain a cobalt carbon nitrogen catalyst, recorded as Co NP / CN-2.

[0046] The catalyst Co obtained in this comparative example NP / CN-2 was analyzed by inductively coupled plasma emission spectroscopy. The results showed that Co NP The Co content in the / CN-2 catalyst is 14.04wt%.

[0047] The catalyst Co obtained in this comparative example NP / CN-2 was tested for acid resistance: Under the condition of pH=3.05, the prepared catalyst Co NP / CN-2 was subjected to dimethyl-NAU hydrogenation experiment, as follows:

[0048] Dimethyl-NAU (85 mg), Co NP / CN-2 catalyst (35 mg) and sulfuric acid solution (20 mL) with a pH of 3.05 were added to a 50 mL polytetrafluoroethylene autoclave in sequence, sealed, replaced with H2 for 3 to 6 times, and then H2 was introduced until the partial pressure reached 1.0 MPa. The reaction system was kept at 40°C for 2 hours with a stirring speed of 400 rpm. After the reaction was completed, the reaction solution was analyzed by liquid chromatography. The catalyst was recovered by centrifugation and the next recycling experiment was carried out. Similarly, the test results after several cycles are shown in the figure below. Figure 6 As shown. Figure 6 It can be seen that the catalyst Co prepared in this comparative example NP The conversion rate of / CN-2 decreased by 25.5% after 8 cycles.

[0049] The above recycling results show that the catalyst Co in Example 1 SA / CNComparative Example 1 Catalyst Co NP / CN-1 and Comparative Example 2 Catalyst Co NP / CN-2 has better stability under acidic conditions. These results indicate that the lower the zinc content, the greater the aggregation of cobalt particles and the formation of cobalt nanoparticles. The addition of Zn can well control the spatial spacing between Co atoms; at the same time, during the pyrolysis process, the coordination effect between N atoms and Co atoms is beneficial to improve the stability of Co single atoms.

[0050] Comparative Example 3

[0051] Commercially available Raney nickel catalyst was selected to carry out dimethyl-NAU hydrogenation experiments under different acidic conditions.

[0052] Under the condition of pH=3.05, a commercially available Raney nickel catalyst was selected to carry out a dimethyl-NAU hydrogenation experiment, as follows:

[0053] Dimethyl-NAU (85 mg), Raney nickel catalyst (2.8 mg), and sulfuric acid solution (20 mL) with a pH of 3.05 were added to a 50 mL polytetrafluoroethylene autoclave in sequence, sealed, replaced with H2 for 3 to 6 times, and then H2 was introduced until the partial pressure reached 1.0 MPa. The reaction system was maintained at 40°C for 2 hours with a stirring speed of 400 rpm. After the reaction was completed, the reaction solution was analyzed by liquid chromatography. The reaction solution was poured out and the above operation was repeated for a cycle experiment. The cycle test results are shown in Figure 7 As shown. Figure 7 It can be seen that the conversion rate of the commercially available Raney nickel catalyst used in industry dropped from 78.4% to 23.6% after being reused only 6 times. Figure 4The comparison further illustrates that the Co prepared in Example 1 SA / CN catalyst has better stability in an acidic environment (pH=3.05) and can be recycled for many times.

[0054] Under the condition of pH=1.95, a commercially available Raney nickel catalyst was selected to carry out the dimethyl-NAU hydrogenation experiment, as follows:

[0055] Dimethyl-NAU (85 mg), Raney nickel catalyst (2.8 mg), and sulfuric acid solution (20 mL) with a pH of 1.95 were added to a 50 mL polytetrafluoroethylene autoclave in sequence, sealed, replaced with H2 for 3 to 6 times, and then H2 was introduced until the partial pressure reached 1.0 MPa. The reaction system was maintained at 40°C for 2 h with a stirring speed of 400 rpm. After the reaction was completed, the resulting reaction solution was analyzed by liquid chromatography. The reaction solution was poured out and the above operation was repeated for a cycle experiment. The cycle test results are shown in Figure 2. Figure 8 As shown. Figure 8 It can be seen that the catalyst Co obtained in Example 1 of the present invention SA After the / CN catalyst was reused 10 times, the conversion rate of the reaction only dropped from 56.9% to 41.0%, while the conversion rate of the Raney nickel catalyst dropped sharply from 96.7% to 15.6% after being reused 6 times. SA / CN catalyst has better acid resistance than Raney nickel catalyst. SA / CN catalyst has good dispersibility in water solvent and can effectively avoid the agglomeration phenomenon in the Raney nickel catalytic process, which will help to realize the industrial application of the system.

[0056] The above description is only a preferred specific implementation manner of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the scope of protection of the invention.

Claims

1. A method for preparing an acid-resistant atomic-level dispersed cobalt carbon-nitrogen catalyst, characterized in that it comprises: Follow these steps: (1) dissolving cobalt nitrate hexahydrate and zinc nitrate hexahydrate in a solvent to obtain a mixed metal salt solution; dissolving 2-methylimidazole in a solvent to obtain a 2-methylimidazole solution; adding the mixed metal salt solution dropwise to the 2-methylimidazole solution, and stirring uniformly at room temperature; collecting the obtained precipitate, centrifuging, washing, and vacuum drying to obtain a powder; (2) placing the powder obtained in step (1) in a tube furnace, heating it to 700-1100° C. in flowing nitrogen, keeping it at this temperature for 1-4 hours, and then cooling it to room temperature to obtain a solid powder; (3) Etching the solid powder obtained in step (2) in an acidic solution to obtain an acid-resistant atomically dispersed cobalt carbon nitrogen catalyst.

2. The method for preparing the acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst according to claim 1, characterized in that: In step (1), the molar ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is 1:

10.

3. The method for preparing the acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst according to claim 1, characterized in that: The solvent selected in step (1) is methanol.

4. The method for preparing the acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst according to claim 1, characterized in that: The molar ratio of the mixed metal salt to 2-methylimidazole in step (1) is 1:2 to 1:

5.

5. The method for preparing the acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst according to claim 1, characterized in that: In step (2), the calcination temperature in nitrogen is 800° C. and the constant temperature holding time is 3 hours.

6. The method for preparing the acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst according to claim 1, characterized in that: In step (3), the acidic solution is hydrochloric acid or sulfuric acid solution, with a pH of 1 to 2; the volume ratio of the solid powder mass to the acidic solution is 1 to 5 mg / mL, and the etching time is 12 to 48 hours.

7. Acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst prepared by the method of claims 1 to 6.

8. Use of the acid-resistant atomically dispersed cobalt carbon-nitrogen catalyst according to claim 7 in the hydrogenation reaction of dimethyl-NAU.

9. The use according to claim 8, characterized in that: The catalyst is used in the reaction of preparing dimethyl-DAU by hydrogenating dimethyl-NAU under acidic conditions, wherein the pH under the acidic conditions is 1-4.

10. The use according to claim 9, characterized in that: The catalytic reaction process is as follows: dimethyl-NAU, catalyst, and acid solution with pH=1-4 are added into a polytetrafluoroethylene high-pressure reactor in sequence, sealed, and the air is replaced by H2 for 3-6 times, and then H2 is introduced to 1.0MPa; the reaction system is maintained at 20-80°C for 2h, and the stirring speed is 400rpm; after the reaction is completed, the obtained reaction solution is analyzed by liquid chromatography, and the catalyst is recovered by centrifugation.

Citation Information

Patent Citations

  • Preparation method of caffeine intermediate N,N-1,3-dimethyl-4,5-diamido urazine

    CN104003941A

  • Preparation method and application of wet-based carbon-supported nano noble metal catalyst

    CN113058590A